Alcohol consumption and smoking in relation to psoriasis: a Mendelian randomization study. (16th August 2022) - Wei, Jiahe; Zhu, Jiahao; Xu, Huiqing; Zhou, Dan; Elder, James T.; Tsoi, Lam C.; Patrick, Matthew T.; Li, Yingjun
Abstract: Background: Alcohol consumption and smoking have been reported to be associated with psoriasis risk. However, a conclusion with high‐quality evidence of causality could not be easily drawn from regular observational studies. Objectives: This study aims to assess the causal associations of alcohol consumption and smoking with psoriasis. Methods: Genome‐wide association study (GWAS) summary‐level data for alcohol consumption ( N = 941 280), smoking initiation ( N = 1 232 091), cigarettes per day ( N = 337 334) and smoking cessation ( N = 547 219) was obtained from the GSCAN consortium (Sequencing Consortium of Alcohol and Nicotine use). The GWAS results for lifetime smoking ( N = 462 690) were obtained from the UK Biobank samples. Summary statistics for psoriasis were obtained from a recent GWAS meta‐analysis of eight cohorts comprising 19 032 cases and 286 769 controls and the FinnGen consortium, comprising 4510 cases and 212 242 controls. Linkage disequilibrium score regression was applied to compute the genetic correlation. Bidirectional Mendelian randomization (MR) analyses were conducted to determine casual direction using independent genetic variants that reached genome‐wide significance ( P < 5 × 10 –8 ). Results: There were genetic correlations between smoking and psoriasis. MR revealed a causal effect of smoking initiation [odds ratio (OR) 1·46, 95% confidence interval (CI) 1·32–1·60, P = 6·24E‐14], cigarettes per day (OR 1·38, 95% CI 1·13–1·67, P = 0·001) and lifetime smoking (OR 1·96, 95% CI 1·41–2·73, P = 7·32E‐05) on psoriasis. Additionally, a suggestive causal effect of smoking cessation on psoriasis was observed (OR 1·39, 95% CI 1·07–1·79, P = 0·012). We found no causal relationship between alcohol consumption and psoriasis ( P = 0·379). The reverse associations were not statistically significant. Conclusions: Our findings provide causal evidence for the effects of smoking on psoriasis risk. What is already known about this topic? Alcohol consumption and smoking have been reported to be associated with psoriasis risk. Whether alcohol consumption and smoking have a causal effect on psoriasis risk remains unclear. What does this study add? This Mendelian randomization study shows a causal association between smoking, but not alcohol consumption, and the risk of developing psoriasis. Restricting smoking could be helpful in reducing the burden of psoriasis. Abstract : Alcohol consumption and smoking have been reported to be associated with psoriasis risk. However, whether alcohol consumption and smoking have causal effect on psoriasis risk remains unclear. This Mendelian randomization study shows a causal association between smoking, but not alcohol consumption, and the risk of developing psoriasis, suggesting restricting smoking could be helpful in reducing the burden of psoriasis. Linked Comment: L. Naldi and S. Cazzaniga. Br J Dermatol 2022; 187:632–633 .